Midsummer knight - Rogers, Gregory (New Milford, Conn. : Roaring Brook Press, 2007)
A bear is rescued by a fairy in an enchanted wood and agrees to return the favor by leading the battle against a usurper who has imprisoned the king and queen, along with their loyal subjects, in the dungeon of their castle.
"A Neal Porter book."
Keywords: Bears -- Juvenile fiction; Fairies -- Juvenile fiction; Heroes -- Juvenile fiction; Stories without words